2018
DOI: 10.1002/jcb.27532
|View full text |Cite|
|
Sign up to set email alerts
|

Matrix stiffness mediates stemness characteristics via activating the Yes‐associated protein in colorectal cancer cells

Abstract: Matrix stiffness is an essential physical microenvironment in solid cancer. However, its influence on cancer stemness still remains elusive. Colorectal cancer (CRC) cell line HCT-116 was cultured in the matrix with various stiffness. The siYAP was applied to detect the changes of stemness markers. The cancer stemness markers, Yes-associated protein (YAP), Lamin A/C and downstream protein molecules, and their activation were measured after the treatment with anti-β1-integrin and FAK inhibitors. In CRC tissue sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 30 publications
0
45
0
Order By: Relevance
“…Most of the main mechanosensitive phenotypes induced through YAP/TAZ lean on integrin-mediated adhesion [11]. YAP and TAZ can also be directly regulated by the extracellular matrix (ECM) stiffness and YAP itself is involved in FA assembly [15,20,21] (Figure 1).…”
Section: Mechanotransduction: Overview and Structural Basismentioning
confidence: 99%
“…Most of the main mechanosensitive phenotypes induced through YAP/TAZ lean on integrin-mediated adhesion [11]. YAP and TAZ can also be directly regulated by the extracellular matrix (ECM) stiffness and YAP itself is involved in FA assembly [15,20,21] (Figure 1).…”
Section: Mechanotransduction: Overview and Structural Basismentioning
confidence: 99%
“…31 In order to explore the effects of matrix stiffness on cancer stem cells and whether YAP activity was involved, we have recently conducted a series of experiments. 32 In our experiment, we found that ECM stiffness remarkably upregulates the expression of CSC markers. Further experiment showed that matrix stiffness can increase the amount of dephosphorylated YAP and its entry into the nucleus.…”
Section: Effect Of Matrix Stiffness On the Characteristics Of Cancer mentioning
confidence: 49%
“…In line with these observations, some studies have correlated the different expression of extracellular matrix proteins and its stiffness to aberrant activation of the TGF-β pathway, accompanied by an expression of determined integrins, with enhancing cancer cell stemness and invasion [67][68][69]. In addition, tumor-initiating cells are more resistant to detachment-induced anoikis and exhibit phenotypic plasticity to move between epithelial to mesenchymal states [69,70].…”
Section: Discussionmentioning
confidence: 85%
“…In addition, tumor-initiating cells are more resistant to detachment-induced anoikis and exhibit phenotypic plasticity to move between epithelial to mesenchymal states [69,70]. Tumor-initiating cells are the driver for drug resistance, cancer relapses, and metastasis, which remains to occur in some cases of breast cancer [69][70][71]. Taken together, this evidence suggests a tight association among the EMT phenotype induced by MDA-MB-231-derived extracellular matrix, through αvβ3 integrin activity and tumor-initiating cells, but further investigation is required in future studies.…”
Section: Discussionmentioning
confidence: 99%